2015
DOI: 10.1002/pat.3710
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of scratch resistance and mechanical properties in wollastonite-reinforced polypropylene copolymers

Abstract: The aim of this research was to establish a balance between scratch resistance and scratch damage visibility in the wollastonite-filled heterophasic polypropylene copolymers.The influences of various factors including the surface hardness, elasticity, friction coefficient, and combinations thereof on the scratch behavior (scratch resistance and scratch visibility) were elucidated. Using micro-scale and nano-scale scratch tests and image analysis techniques, the scratch hardness, scratch depth, and scratch visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The results of dynamic mechanical analysis with higher storage and loss modulus of PP composites supported the reinforcing ability of wollastonite. However, a different finding was obtained by Sobhani and Khorasani, where it is found the introduction of wollastonite into PP copolymer matrix contributed to ductile fracture behavior of the composites and leaded to enhancement in elongation at break up to 30%. The ductile fracture occurred in this study might due to the good interfacial interaction and formation of new crystalline structure in PP copolymer induced by wollastonite, which facilitated the stress transfer and allow occurring of plastic deformation in the polymer matrix.…”
Section: Tensile and Flexural Properties Of Polymer Compositesmentioning
confidence: 80%
See 1 more Smart Citation
“…The results of dynamic mechanical analysis with higher storage and loss modulus of PP composites supported the reinforcing ability of wollastonite. However, a different finding was obtained by Sobhani and Khorasani, where it is found the introduction of wollastonite into PP copolymer matrix contributed to ductile fracture behavior of the composites and leaded to enhancement in elongation at break up to 30%. The ductile fracture occurred in this study might due to the good interfacial interaction and formation of new crystalline structure in PP copolymer induced by wollastonite, which facilitated the stress transfer and allow occurring of plastic deformation in the polymer matrix.…”
Section: Tensile and Flexural Properties Of Polymer Compositesmentioning
confidence: 80%
“…Improvement in impact strength of the PP copolymer was observed when wollastonite was incorporated . Work of Hadi et al revealed that impact strength of both calcium carbonate‐ and wollastonite‐reinforced PP composites increased with the filler content but wollastonite contributed greater enhancement…”
Section: Impact Properties Of Polymer Compositesmentioning
confidence: 89%
“…Even a few scratches, though most of them are a few micrometers in depth, can deteriorate the original appearance [3] and in some cases, may even affect functionality by rendering them more vulnerable to other types of strain (flexion, impact, fatigue, etc.) [4]. Hence, scratch resistance and scratch visibility are very important factors for the top functional coatings in laminate floors.…”
Section: Introductionmentioning
confidence: 99%
“…When these flaws on the damaged surface are larger than the wavelength of visible light, the scratches become visible [7]. The scratch visibility is known to correlate well with parameters like scratch hardness, scratch depth, surface roughness on the scratch path [6], coefficient of friction of the surface, and filler-matrix interface strength as well as the elastic recovery characteristics of the polymer [4]. The damage caused by plastic flow generally has a lower impact on the scratch visibility than brittle damage due to less scattered light [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation